(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article discusses communicative language teaching method to teach English for second language learners. The author highlights the goal of CLT, which is to develop learners’ ability to communicate effectively in real-life situations and emphasizes the focus on using language for authentic purposes, rather than simply memorizing grammar rules.